Comparison of chondrosarcoma cases: current clinical situations among institutions - Jami, Sayed Abdulla; Jiandang, Shi; Hao, Liu Chang; Xi, Zhu; Wenqi, Yuan; Zhou, Zhanwen (International Journal of Health Sciences, 2021)
Objective: Chondrosarcoma is a rare tumor that has a variable biological characteristic, and its treatment is controversial. We performed a comparison review of different regional institutions series to assess the clinical outcome of patients. Methods: A retrospective review of 33 chondrosarcomas (Grades I, II, and III) patient data since 2013, compared with 15 author’s total 868 patients published literature results to find more about clinical and statistical advantages and similarities with author institute cases. Here is the mentioning of clinical information, surgery type categorized, adjuvants types, genders, follow-up years, recurrence, affected areas, death rates, successful outcome, and survival rates using statistical methods. Results: The overall survival rate was 94%, successful outcome 85% in 4.3±1.2 years follow-up. Observed wide resection, distilled water as adjuvant, chemo and radiotherapy significantly shows excellent results over our compared chondrosarcoma literature data. We have also marked that females and humerus bone are more affected by chondrosarcoma among those literature data. Conclusions: Low-grade chondrosarcoma of the skeleton can be treated with wide resection. Using distilled water give good oncological outcome and a very low rate of post-surgical complications for chondrosarcoma all grades recurrence.